2014
DOI: 10.1080/08897077.2014.954027
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Impairment in Cannabis- and Opioid-Dependent Adolescents

Abstract: Working memory impairment was substantial in treatment-seeking youth with primary cannabis and opioid dependence (the latter actually having comparable rates of cannabis use), and significantly more pronounced in the primary cannabis-dependent group. Without an assessment of working memory prior to substance exposure, the differential contributions of substance-induced vs. preexisting impairment are unclear. Lower scores in the cannabis group may reflect lower socioeconomic status (SES), which is typically cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…Early optimism related to the potential benefits of PrEP may be diminished with regard to certain risk populations, however, due to evidence suggesting that even modest or occasional non-adherence can greatly lessen the effects of PrEP [25, 27, 28]. Particularly with regard to high-risk people who use drugs, the combination of substance abuse and higher levels of neuropsychological symptoms may significantly affect their adherence to PrEP, engagement and retention in HIV interventions as well as their ability to acquire and retain the knowledge and skills necessary to modify their risky behaviors [1620]. Therefore, incorporation of innovative tools to improve medication adherence, health-promoting behaviors, and access to and utilization of health care are urgently needed, particularly tailored toward people who use drugs with NCI.…”
Section: Introductionmentioning
confidence: 99%
“…Early optimism related to the potential benefits of PrEP may be diminished with regard to certain risk populations, however, due to evidence suggesting that even modest or occasional non-adherence can greatly lessen the effects of PrEP [25, 27, 28]. Particularly with regard to high-risk people who use drugs, the combination of substance abuse and higher levels of neuropsychological symptoms may significantly affect their adherence to PrEP, engagement and retention in HIV interventions as well as their ability to acquire and retain the knowledge and skills necessary to modify their risky behaviors [1620]. Therefore, incorporation of innovative tools to improve medication adherence, health-promoting behaviors, and access to and utilization of health care are urgently needed, particularly tailored toward people who use drugs with NCI.…”
Section: Introductionmentioning
confidence: 99%
“…Prior evidence has demonstrated that HIV-infected PWUDs display a wide range of cognitive deficits including problems with executive function, attention, memory, new learning, information-processing speed, and visual-spatial perception, that have significant impact on HIV risk behaviors and risk-reduction intervention outcomes. Furthermore, the presence of cognitive impairment may be associated with the disease process (AIDS-related dementia), drug use history, or relatively poor lifestyle (Anand, Springer, Copenhaver, & Altice, 2010; Anderson, Higgins, Ownby, & Waldrop-Valverde, 2015; Attonito, Devieux, Lerner, Hospital, & Rosenberg, 2014; Becker, Thames, Woo, Castellon, & Hinkin, 2011; Byrd et al, 2011; Ezeabogu, Copenhaver, & Potrepka, 2012; Heaton et al, 2011; Meade, Conn, Skalski, & Safren, 2011; Schouten, Cinque, Gisslen, Reiss, & Portegies, 2011; Shrestha, Weikum, Copenhaver, & Altice, 2016; Thaler, Sayegh, Kim, Castellon, & Hinkin, 2015; Woods, Moore, Weber, & Grant, 2009; Zhou &Saksena, 2013) and may be disruptive to participation in treatment services, including HIV prevention, treatment engagement, and medication adherence, which must be accounted for during behavioral intervention development and adaptation (Bates, Pawlak, Tonigan, & Buckman, 2006; Fishbein et al, 2007; Huedo-Medina, Shrestha, &Copenhaver, 2016; Shrestha & Copenhaver, 2016; Shrestha, Huedo-Medina, & Copenhaver, 2015; Verdejo-Garcia & Perez-Garcia, 2007; Vo, Schacht, Mintzer, & Fishman, 2014). …”
mentioning
confidence: 99%
“…Adherence to ART by PWUDs is challenging, however, due to distinct concerns faced by drug users, such as regimen complexity, pill burden, side effects, untreated depression, substance use, and lack of social support (Ammassari et al, 2001; Bartlett, 2002; Bartlett, DeMasi, Quinn, Moxham, & Rousseau, 2001; Wagner et al, 2011). PLWH, and particularly PWUDs with HIV infection, are at increased risk of experiencing NCI such that it may significantly impede their abilities to partake fully in treatment services, treatment engagement, and ART adherence (Bates et al, 2006; Fishbein et al, 2007; Shrestha, Huedo-Medina, et al, 2015; Verdejo-Garcia & Perez-Garcia, 2007; Vo et al, 2014). …”
mentioning
confidence: 99%
“…As a result of chronic drug use, related lifestyle experiences, and relatively poor health (717), a disproportionate percentage of PWUDs experience neurocognitive impairment (NCI) to the extent that it may interfere with their ability to fully participate in treatment (1820). It is well documented that HIV-infected PWUDs may experience cognitive impairment associated with the disease process (AIDS-related dementia) (1417, 19, 2127), but HIV- PWUDs also demonstrate levels of NCI that may be disruptive to their participation in treatment services (18, 2831). Numerous primary and secondary HIV prevention approaches exist (see https://effectiveinterventions.cdc.gov/ http://www.nrepp.samhsa.gov/ProgramProfile.aspx?id=11) (32) but no studies have examined how NCI may influence intervention or treatment outcomes among PWUDs.…”
Section: Introductionmentioning
confidence: 99%